The impact of employment contract to the employee performance: A case study of MIC (T) Ltd (Tigo company) in Morogoro region - Tusemen, Herris Harrison (Mzumbe university, 2024)
A dissertation submitted to Mzumbe University as a partial fulfilment for the award of the degree of Masters Degree of Business Administration in Corporate Management (MBA-CM) of Mzumbe University.